Membangun Semangat Entrepreneur Muda di Tengah Revolusi Digital - Muh. Syata, Wahyu; Hikmayani Subur; Murni Nia (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The digital revolution has changed how young generations view the world of work and opened up new opportunities for the emergence of digitalpreneurs who rely on creativity, innovation, and technology. Youth entrepreneurship is a major force behind digital change, but its implementation is influenced by a number of barriers and personal growth expectations. This research aims to analyze the factors influencing the entrepreneurial spirit of young people in the digital era and the strategies that can be implemented to foster the growth of digital entrepreneurial interest. The research method used is a literature study, examining previous research findings, theories, and relevant scientific publications. The study results indicate that interest in digital entrepreneurship is influenced by a combination of internal factors such as self-efficacy, motivation, digital literacy, and risk-taking behavior, as well as external factors such as social support, education, business environment, government policies, and technological developments. Formal education, mentoring programs, and the use of digital technology have proven effective in fostering the entrepreneurial spirit of young people. However, young entrepreneurs also face various challenges, including limited practical experience, intense competition in the digital market, and limited access to capital and information. This research underscores the importance of developing a supportive entrepreneurial ecosystem based on education, technology, and collaboration to maximize the entrepreneurial potential of the younger generation amidst digital transformation